Isolation of Pseudomonas sp. strain CCA1 from leaf soil and preliminary characterization its ligninolytic activity - Akita, Hironaga; Kimura, Zen-ichiro; Mohd Yusoff, Mohd Zulkhairi; Hoshino, Tamotsu (JSciMed Central, 2016)
Here we describe the screening and characterization of a lignin-degrading bacterium from an environmental sample. The bacterium was isolated from leaf soil and identified as Pseudomonas sp. strain CCA1 based on 16S rRNA gene sequencing. Although identified as able to degrade lignin in our screen, the ligninolytic activityof this strain was weak. Nonetheless, assessment of its utilization of lignin-associated aromatic monomers revealed that Pseudomonas sp. strain CCA1 assimilated at least ten lignin-associated aromatic monomers.